Multidimensional Curriculum Development and Management Model for Pesantren: A Strategic Approach to Counteract Radicalism - Ghazali, Raisul Umam (el-Tarbawi, 2024)
Amid the threat of radicalism and terrorism in Indonesia, Islamic boarding schools are often viewed as breeding grounds for radical groups. This study examines the multidimensional approach in the curriculum of Pondok Pesantren Darul Ishlah Tulang Bawang, Indonesia, to counter radicalism. A case study design involving in-depth interviews, observations, and documentation was employed for this study. The results of this study indicate the need for the integration of moderate values in the pesantren curriculum and activities. This included the enrichment of materials related to life skills. This study also underlines the importance of professionalism in the development of pesantren management through public involvement and technology integration. In addition, regulatory strengthening, government supervision, and cooperation between pesantrens and related institutions are other substantial findings of the study. This multidimensional approach is relevant to prevent pesantrens from becoming hotbeds of radicalism. This encourages the generation of peace agents. A detailed elaboration of efforts to prevent radicalism and terrorism in Indonesia through the pesantren curriculum and management is provided in the study.